Underwater asynchronous navigation using single beacon based on the phase difference. (15th January 2021) - Sun, Sibo; Zhang, Xinyu; Zheng, Ce; Zhao, Chunhui; Fu, Jin
Abstract: Asynchronous navigation has a more flexible application area compared with synchronous methods. However, the precision of the asynchronous navigation is low, especially for the single beacon navigation due to the improperly geometrical configuration. In this paper, we address a high-precision asynchronous navigation method using single beacon for autonomous underwater vehicle (AUV). Firstly, the coordinate-solving equations are established utilizing the synchronization-free phase difference (PD) information and time-difference-of-arrival (TDOA) information. Secondly, a scheme to obtain the PD information is proposed via signal alignment, conjugate multiplication, phase unwrapping, and linear fitting (or quadratic fitting), successively. Thirdly, the precision analysis is presented, which shows that the proposed method has a comparable precision compared with synchronous methods. Finally, the effectiveness of the method is validated through several groups of the simulations.